PENGARUH PEMBERIAN KOMBINASI PAKAN PELLET DAN PAKAN HEWANI PADA BUDIDAYA BENIH IKAN GURAMI (Osphronemus gouramy) - Dirmansyah; Salnida Yuniarti Lumbessy; Dewi Putri Lestari (Journal of Fish Nutrition, 2022)
The purpose of this study was to determine the effect of a combination of pellet feed and animal feed on the growth and survival of gouramy (O. gouramy) fry. This research was carried out for 60 days in the fish production and reproduction laboratory of the aquaculture study program at Mataram University. The method used is an experimental method using a completely randomized design (CRD) with 5 treatments and 3 replications, the treatment being tested is a combination composition of pellet feed and animal feed consisting of P0 = Control, P1 = pellet 25% and golden snail 75% , P2 = 25% pellets and 75% silk worms, P3 = 25% pellets and 75% earthworms, P4 = 25% pellets + 25% snails + 25% silk worms + 25% earthworms). Parameters tested included absolute weight, specific weight growth, absolute length, specific length growth, feed conversion ratio, feed efficiency level, survival rate and water quality (DO, pH, and temperature). The data obtained were then analyzed using variance (ANOVA) with a 95% confidence level. Data that showed a real effect were further tested to determine the best treatment. Water quality data were analyzed descriptively. The results showed that the average absolute weight of carp ranged from 4.45 – 5.26 g, the average growth rate of specific weight ranged from 1.40 – 1.50%/day, the average absolute length ranged from 1.53 – 1.84 cm, the average growth rate was 1.53 – 1.84 cm. specific length growth ranged from 0.37 – 0.45%/day, the average feed conversion ratio value ranged from 3.32-3.71, the average feed utilization efficiency value ranged from 27.31-33.76%, the average survival rate ranged from 60.00 – 73.33 %. all the combination treatments of pellet feed and animal feed gave the same effect as pellet feed treatment (control) on all test parameters so that it could be used as an alternative feed in gouramy cultivation